The self and self-knowledge - Coliva, Annalisa, 1973- (Oxford : Oxford University Press, 2012)
Experts explore the nature of thoughts about ourselves, and the distinctively human ability to know the kind of mental states we enjoy. They adopt a range of perspectives - from the normative to the phenomenological, from neo-expressivism to constitutivism - to deepen our understanding of these central aspects of our mentality.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Self (Philosophy); Self-knowledge, Theory of